PSYCHOLOGICAL AND PEDAGOGICAL MANAGEMENT STUDENT ACTIVITY AS A FORM OF DEVELOPMENT SOCIALLY SIGNIFICANT QUALITIES STUDENTS 'PERSONALITIES (Pedagogy of Higher and Secondary Education, 2007)
The article investigates the influence of psychological and pedagogical guidance of students’ activity in terms of developing qualities which are socially important for a personality.